Microbial astaxanthin: from bioprocessing to the market recognition - Mussagy, Cassamo U.; Kot, Anna; Dufossé, Laurent; Gonçalves, Carmem N. D. P.; Pereira, Jorge F. B.; Santos-Ebinuma, Valeria C. [UNESP]; Raghavan, Vijaya; Pessoa, Adalberto (Springer Nature, 2023)
Abstract: Theattractive biological properties and health benefits of natural astaxanthin (AXT), including its antioxidant and anti-carcinogenic properties, have garnered significant attention from academia and industry seeking natural alternatives to synthetic products. AXT, a red ketocarotenoid, is mainly produced by yeast, microalgae, wild or genetically engineered bacteria. Unfortunately, the large fraction of AXT available in the global market is still obtained using non-environmentally friendly petrochemical-based products. Due to the consumers concerns about synthetic AXT, the market of microbial-AXT is expected to grow exponentially in succeeding years. This review provides a detailed discussion of AXT’s bioprocessing technologies and applications as a natural alternative to synthetic counterparts. Additionally, we present, for the first time, a very comprehensive segmentation of the global AXT market and suggest research directions to improve microbial production using sustainable and environmentally friendly practices. Key points: • Unlock the power of microorganisms for high value AXT production. • Discover the secrets to cost-effective microbial AXT processing. • Uncover the future opportunities in the AXT market.
Keywords: Astaxanthin; Downstream; Haematococcus pluvialis; Health; Market; Microbial sources; Phaffia rhodozyma; Upstream